The crystal structure of 2-amino-3-carboxypyridin-1-ium iodide hemihydrate, C6H8IN2O2.5 - Huang Guang (Zeitschrift für Kristallographie - New Crystal Structures)
C6H8IN2O2.5, monoclinic, P2/n (no. 13), a = 9.8300(4) Å, b = 5.3338(2) Å, c = 17.4040(8) Å, β = 105.493(2)°, V = 879.36(6) Å3, Z = 2, R gt(F) = 0.0139, wR ref(F 2) = 0.0306, T = 150(2) K.